Firm heterogeneity, industry dynamics and climate policy - Ara Jo; Christos Karydas (ETH Zurich, CER-ETH - Center of Economic Research, 2023)
We develop a dynamic general equilibrium model to quantify the interaction between climate policy, industry dynamics, and the elasticity of substitution between clean and dirty energy in the economy. The model incorporates empirical observations that firms differ substantially in their potential for energy substitution and that the economy is growing more capable of substituting clean for dirty energy over time as environmental regulation becomes more stringent. Our model highlights the effect of dynamic industry response on increasing the average elasticity of substitution in the economy due to the exit of least flexible firms in response to climate policy. The higher average elasticity of substitution increases the effectiveness of the policy at reducing emissions, resulting in a 35 percent decrease in the size of the carbon tax required to achieve carbon neutrality.
Keywords: Q40; Q55; Q54; O33; 330; industry dynamics; elasticity of substitution; climate policy